Analysis Of Efficiency And Effectiveness In The Management Of Village Fund Budget In Pagar Gunung Village, Kaur Regency 2022-2023 - Kamelia Astuty; Wahyu Adi Saputra; Oni Yulianti (Universitas Dehasen Bengkulu, 2026)
Village development is an essential part of national development aimed at improving community welfare. Based on Law Number 6 of 2014 concerning Villages, the Village Fund is allocated to every village through the State Budget (APBN) to finance government administration, development implementation, community development, and community empowerment. Pagar Gunung Village, located in Padang Guci Hulu District, Kaur Regency, is one of the villages that receives Village Fund allocations each year to support development and public service activities. This study aims to analyze the level of efficiency and effectiveness in managing the Village Fund in Pagar Gunung Village for the 2022 and 2023 fiscal years. The research method used is descriptive quantitative, employing efficiency and effectiveness ratio analysis based on budget and realization data obtained through observation and documentation. The results show that the management of the Village Fund in Pagar Gunung Village achieved an efficiency level of 100% and an effectiveness level of 100%, indicating that all planned activities were successfully implemented according to the established budget. This demonstrates that the financial management of the Village Fund in Pagar Gunung Village has been carried out optimally and has had a positive impact on community welfare and village development.